Competitive Intelligence in Malaysia Pharmaceutical Industry : Effectiveness of Implementation - Ooi, Hooi Min (2004)
Competitive Intelligence is increasingly being considered an important, if not mandatory, piece of every business’ overall strategy and functioning, including tactical and strategic planning. The level of Competitive Intelligence activities differ by industries, and at different stage of product life cycle. It is closely linked to Knowledge Management – another major field on the way company handling information. Competitive Intelligence has often been related to industrial espionage where some find the border unclear. With recent emphasis on the ethical and legal boundaries, Competitive Intelligence has slowly stand on it own feet. The terminology of “Competitive Intelligence”, however, is still being an unfamiliar aspect to a numbers of manager and personnel in corporate world and a lot of misconceptions have been placed on it. While it takes a simple four basic steps to build a cycle of Competitive Intelligence: Planning, Collection, Analysis and Dissemination; obstacles have arose at each stage. Being a highly competitive industry, pharmaceutical industry is heavily relying on the gathering of competitor information to ensure fast moveradvantage and maintain competitive edge to sustain business success. Pharmaceutical industry in Malaysia is relatively a small market comparing to global pharmaceutical industry, yet the activities of Competitive Intelligence is aggressive. The success of implementation of Competitive Intelligence lies on few factors, including the setting of market environment and some organizational setting.